Comparative and phylogenetic analyses using mitogenomes revealed gene re-arrangement of Boletaceae (Boletales) - Xianyi Wang; Jiawei Tao; Zhongyao Guo; Guoyu Wang; Guangyin Xu; Yaping Wang; Yaohang Long; Hongmei Liu (IMA Fungus)
Boletaceae, the largest family in the Boletales order, is an ecologically and economically important group and the phylogenetic studies of this group need to be further developed. The mitogenome is an effective molecular marker for analysing phylogenetic relationships; however, Boletaceae mitochondrial genome (mitogenome) has been studied to a lesser extent. Thus, a comparative analysis of the mitogenomic features of seven Boletaceae species, representing seven distinct genera, was conducted. Phylogenetic relationships amongst these species within Boletales were reconstructed, based on the mitogenomic data. Highly consistent phylogenetic results within 34 Boletales species and two outgroups from Polyporales, based on mitogenomic datasets, were obtained using Maximum Likelihood and Bayesian Inference methods. Results of phylogenetic analyses revealed that Boletus, Retiboletus and Neoboletus were polyphyletic. Interestingly, species of Neoboletus with different bruising discolouration patterns were found in separate clades, suggesting this trait may reflect underlying genetic divergence. Furthermore, comparative and phylogenetic analyses revealed gene re-arrangements in mitogenomes of Boletaceae. This study is the first to report on complete mitogenomes of four genera (Amoenoboletus, Hourangia, Leccinum and Strobilomyces) and will help better understand the phylogenetic relationships of Boletales. Furthermore, addition of more new taxa is necessary to reconstruct a high-resolution tree.